PTU-259 Routine biopsy during lower gi endoscopy is of diagnostic value for patients with chronic diarrhoea. (22nd June 2015) - Trembling, PM; Nicol, F; Hoare, J
Abstract : Introduction: Patients investigated for chronic diarrhoea often have normal lower GI endoscopy, and mucosal biopsies are recommended, although their clinical value is controversial. We assessed the diagnostic yield of mucosal biopsies in patients undergoing lower GI endoscopy for investigation of chronic diarrhoea. Method: All lower GI endoscopies performed in a large multi-site hospital trust over a period of one month for chronic diarrhoea were identified using the endoscopy reporting system and retrospectively analysed. Only procedures where mucosal biopsies were taken were included. The macroscopic endoscopic findings were recorded and correlated with histology findings. Results: 110 endoscopic procedures were identified. The mean age of patients was 53 (range 19–85), 50% were male. The endoscopic findings were; normal (60%), polyp (s) (17%), colitis/inflammation (8%), polyp (s) and diverticular disease (7%), diverticular disease (6%), tumour (2%). In the group with normal mucosa (n = 65), prevalence of microscopic pathology was 23% (colitis 9.2%, lymphocytic colitis 7.7%, likely drug reaction 3.1%, eosinophilia 1.5%, melanosis coli 1.5%). In the cohort where no polyps were detected, sensitivity for lower GI endoscopy identifying pathology seen on biopsy was 29% (95% CI; 11.4–52.2%), specificity 81% (95% CI; 68.6–89.6%). Conclusion: Our findings report a prevalence of histological abnormality in patients with chronic diarrhoea and normal lower GI endoscopy that is at the higher end of prevalence reported in other series. 1–5 These data support the role of routine biopsy in this group of patients. The practice of routine biopsy in this cohort of patients is further supported by the low sensitivity in identifying abnormalities at endoscopy. The high prevalence of colitis and lymphocytic colitis identified histologically demonstrates the clinical value of biopsy in directly informing treatment decisions. Disclosure of interest: None Declared. References: Patel Y, Pettigrew NM, Grahame GR, Bernstein CN. The diagnostic yield of lower endoscopy plus biopsy in nonbloody diarrhea. Gastrointestinal Endosc. 1997;46(4):338–43 Shah RJ, Fenoglio-Preiser C, Bleau BL, Giannella RA. Usefulness of colonoscopy with biopsy in the evaluation of patients with chronic diarrhea. Am J Gastroenterol. 2001;96(4):1091–5 Hotouras A, Collins P, Speake W, Tierney G, Lund JN, Thaha MA. Diagnostic yield and economic implications of endoscopic colonic biopsies in patients with chronic diarrhoea. Colorectal Dis. 2012;14(8):985–8 Sidhu PS, Khan F, Hebden J, Donnelly M. Colonic biopsies to detect microscopic colitis in patients with diarrhoea and "normal" colonoscopy: worth the effort? Gut 2012;61 :A372 Yusoff IF, Hoffman NE, Ormonde DG. Is routine mucosal biopsy of value in patients with diarrhoea and normal colonoscopy in an open access setting? Gastrointestinal Endosc. 2000:51 (4):AB146